PENGARUH REPUTASI, DAN ELEKTRONIC WORD OF MOUTH TERHADAP KEPERCAYAAN PELANGGAN SHOPEE - Rizki Ramadani; Khairul Bahrun (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
The objective of this research is to determine the influence of reputation and electronic word of mouth on consumer trust among Shopee customers among Management Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The population used in this research consists of 120 Management Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The sampling technique used was purposeful sampling based on established criteria, involving 120 respondents. Data collection techniques included observation, documentation, and questionnaires. The processed data were analyzed using SPSS 24 formulas. Based on the research results and analysis of the influence of the variables Reputation and Electronic Word of Mouth  on Customer Trust in Shopee Customers among Management Program Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu,  the  following  conclusions  can  be  drawn:  Reputation   has  a  positive  and significant effect on Customer Trust  among Shopee customers among Management Program students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. Keywords: Reputation, Electronic Word of Mouth, Consumer Trust